Resistensi Kelompok Minoritas Keagamaan Jemaat Ahmadiyah Indonesia - Dewi Nurrul Maliki (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2010)
This paper explores the contestation among islamic sub-altern communities and islamic mainstream communities. It discusses two important things. First, the forms of resistance of Jemaat Ahmadiyah Indonesia (JAI) of Yogyakarta toward the practice of minoritization. Second, how the Yogyakarta city, which best known as a tolerance city, facilitate the dialogue among islam communities. This paper conclude that the resistance of JAI of Yogyakarta is a respond toward minoritization employed by islamic mainstream communities. In this case, the JAI of Yogyakarta has succeed in mobilizing supports from their external network of academic groups and civil society organizations.